DECODING AMBITIONS: A STUDY ON THE PERCEPTIONS AND CAREER INTENTIONS OF UNDERGRADUATE NURSING STUDENTS - Esievo, Jane Ngozi; Afolayan, David Olumide (American Research Journal of Nursing and Health Sciences (ARJNHS), 2024)
Nursing, as defined by the American Nurses Association, encompasses the protection, promotion, and optimization of health and abilities, the prevention of illness and injury, the alleviation of suffering through the diagnosis and treatment of human response, and advocacy in the care of individuals, families, communities, and populations. However, the nursing workforce in Nigeria has faced a significant challenge in recent years. According to a November 2022 report in the Punch newspaper, an alarming 57,000 nurses migrated from Nigeria to seek better opportunities abroad between 2017 and 2022. This mass exodus poses a serious threat to the nation's healthcare system and calls for immediate attention and strategic interventions. The migration of such a substantial number of nurses has contributed to a growing global imbalance in the supply and demand of nursing professionals. This issue is further exacerbated by the ongoing COVID-19 pandemic, which has placed an unprecedented strain on healthcare systems worldwide. The pandemic has not only highlighted the critical role of nurses but has also intensified the challenges they face, including occupational infections, stress, and burnout. Consequently, addressing the global nursing shortage has become an urgent imperative for maintaining the integrity of healthcare delivery systems. This paper aims to explore the multifaceted dimensions of the nursing shortage issue, with a specific focus on Nigeria. By examining the root causes of nurse migration, the paper seeks to shed light on the systemic challenges faced by the Nigerian healthcare system that drive nurses to seek employment opportunities abroad. Additionally, the study will assess the broader global context, considering the impact of the nursing shortage on healthcare delivery during health crises such as the COVID-19 pandemic. The findings of this research will contribute to a comprehensive understanding of the complex factors influencing nurse migration and the subsequent shortage. Moreover, it will inform evidence-based strategies and policies to retain and attract nursing professionals, not only in Nigeria but also in other regions grappling with similar challenges. By addressing the systemic issues that underlie nurse migration, stakeholders can work collaboratively to create a more sustainable and resilient nursing workforce, ensuring the provision of quality healthcare services for all.